Association between emotional state and tinnitus severity in a sample of 53 participants: Emotional state and tinnitus severity - Fernández Ledesma, Marta; Sanz-Fernández, Ricardo; Cuesta Ruiz, María; Cobo Parra, Pedro (Auditio, 2024)
Tinnitus is the perception of sound in the absence of an identifiable internal or external sound source. This symptom affects approximately 14% of the adult population, with prevalence increasing with age. In this study we evaluated the association between emotional state and tinnitus severity in a sample of 53 participants before they started sound therapy. To assess emotional state, the Hospital Anxiety and Depression Scale (HADS) was used, divided into its two subscales for anxiety (HADA) and depression (HADD). To assess tinnitus severity, the Tinnitus Handicap Inventory (THI) and Tinnitus Functional Index (TFI) were used. The sample population showed a strong positive correlation between the HADA and HADD scales and the THI and TFI questionnaires (r = 0.80 and 0.81, respectively). The results corroborate the association between emotional state and tinnitus severity, emphasising the need for an interdisciplinary treatment approach that covers both physical and emotional aspects.